Tissue culture and phytochemical studies of Podophyllum, Diphylleia and Passiflora species - Silva, Cláudia Gontijo (2000)
Lignans are the most important secondary metabolites known in Podophyllum hexandrum and Diphylleia cymosa. Tissue cultures studies were carried out in order to preserve and increase these germplasms. Somatic embryogenesis in both species was obtained and confirmed histologically. In D. cymosa, somatic embryos were induced from leaf and petiole-derived callus. The formation of abnormal embryos, with fused cotyledons, was influenced by the growth regulators used. Embryo maturation was confirmed histochemically through the identification of starch granules in the cotyledons. Regeneration was dependent on the culture media. Somatic embryogenesis in P. hexandrum was achieved through embryogenic cell suspension cultures from root-derived callus. Organogenesis via adventitious bud formation led to plant regeneration in liquid medium. Phenotypically normal plants were recovered. The regenerant showed the somatic chromosome number of 2n=2x=12, although some chromosomes were morphologically abnormal. The recalcitrance of P. hexandrum towards Agrobacterium-mediated transformation was demonstrated with different strains of both A. tumefaciens and A. rhizogenes. The presence of cytotoxic lignans in P. hexandrum may have a role in the inactivation of the bacteria. Aryltetralin lactone lignans isolated from rhizomes and roots of P. hexandrum and characterized by spectroscopic methods were used as standards in phytochemical studies of D. cymosa. Enzymic hydrolysis of the lignan glycosides, followed by reverse-phase HPLC, allowed the screening of lignans in leaf tissues, calli and cell suspension cultures. The antitumour lignin, podophyllotoxin was detected in young leaves of cultivated plants and. for the first time, in vitro petiole-derived calli. Flavonoids were investigated in leaf extracts of Passiflora edulis, P. incarnate and their somatic hybrids. Fractionation of the crude extracts of P. incarnata and the somatic hybrid SHI led to the isolation of compounds with skeletal type of C-glycosylflavones. Isoorientin was identified in P. edulis. whilst vitexin was found in P. incarnata by TLC. All the somatic hybrids showed similar consistant flavonoid banding profiles. Isoorientin and vitexin were detected in the somatic hybrids. HPLC of the parental species revealed a distinct pattern of flavonoids. Isoorientin was clearly detected in P. edulis, whereas isovitexin was present in both species. The fingerprint patterns of the HPLC separations of the flavonoids were similar in all the somatic hybrids, probably due to the clonal nature of the plants analysed. They appeared to be more closely related to P. incarnata than to P. edulis. However, they also exhibited flavonoids intermediate between those of the parental species. This is the first report of the biosynthesis of isoorientin and isovitexin in these novel somatic hybrids and could provide information about their inheritance.